(untitled) (LEARNing Landscapes, 2016)
A university-community choir is a hybrid of an institutional choir and a community choir, facilitating the creation, consumption, and sharing of art, culture, knowledge, and wealth between its various stakeholder groups. We surveyed and interviewed a variety of stakeholders of a university-community choir to illuminate the mutually bene cial relationships that exist between them. The bene ts of the university- community choir include enabling the artist-researcher-teacher, keeping music in postsecondary liberal arts education, facilitating lifelong music learning and serious leisure, and cultivating future artists. We demonstrate the value of such an organization, as it bridges the university-community divide through music education.